2009
DOI: 10.1093/brain/awp137
|View full text |Cite
|
Sign up to set email alerts
|

Interictal magnetoencephalography and the irritative zone in the electrocorticogram

Abstract: Magnetoencephalography (MEG) is considered a useful tool for planning electrode placement for chronic intracranial subdural electrocorticography (ECoG) in candidates for epilepsy surgery or even as a substitute for ECoG. MEG recordings are usually interictal and therefore, at best, reflect the interictal ECoG. To estimate the clinical value of MEG, it is important to know how well interictal MEG reflects interictal activity in the ECoG. From 1998 to 2008, 38 candidates for ECoG underwent a 151-channel MEG reco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
76
1
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(84 citation statements)
references
References 66 publications
3
76
1
1
Order By: Relevance
“…More recently, it has been described that patients with seizures from the superior parietal region frequently disclosed early involvement of medial temporal lobe structures (Bartolomei et al 2011). Our results agree with other studies showing the difficulty of detecting spikes arising from medial temporal region using gradiometers (Oishi et al 2002;Leijten et al 2003;Enatsu et al 2008;Agirre-Arrizubieta et al 2009;Wennberg et al 2011). However, there are reports of successful MEG recordings from deep sources like the amygdala, using magnetometer pick-up coils characterized by a better sensitivity to deep sources than gradiometers (Moses et al 2007;Enatsu et al 2008).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…More recently, it has been described that patients with seizures from the superior parietal region frequently disclosed early involvement of medial temporal lobe structures (Bartolomei et al 2011). Our results agree with other studies showing the difficulty of detecting spikes arising from medial temporal region using gradiometers (Oishi et al 2002;Leijten et al 2003;Enatsu et al 2008;Agirre-Arrizubieta et al 2009;Wennberg et al 2011). However, there are reports of successful MEG recordings from deep sources like the amygdala, using magnetometer pick-up coils characterized by a better sensitivity to deep sources than gradiometers (Moses et al 2007;Enatsu et al 2008).…”
Section: Discussionsupporting
confidence: 90%
“…It seems that the major reasons for the limited sensitivity of MEG to medial temporal spikes are the rapid decay of the magnetic field with the distance and the convoluted anatomy of medial temporal structures that tends to create closed electric/magnetic fields (Gavaret et al 2004;Santiuste et al 2008;Wennberg et al 2011). Although this is still a subject of debate (Brodbeck et al 2011;Carrette et al2011), MSI seems limited and probably not useful for evaluating medial temporal involvement in focal epilepsy (Agirre-Arrizubieta et al 2009;Wennberg et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Prior studies reported a high proportion of concordance between MEG and intracranial EEG (ICEEG) in localizing the EZ, and researchers have investigated whether preimplantation MEG is useful in guiding the placement of ICEEG electrodes in invasive cases (Sutherling et al, 1988(Sutherling et al, , 2008Smith et al, 2000;Minassian et al, 1999;Mamelak et al, 2002;Stefan et al, 2003;Barkley and Baumgartner, 2003;Baumgartner, 2004;Knowlton et al, 2006Knowlton et al, , 2009RamachandranNair et al, 2007;Agirre-Arrizubieta et al, 2009). Due to the fact that combined MEG and EEG can monitor neuronal activity at different orientation levels, several authors reported an additive value of the combination of both tools during pre-surgical evaluation (Mikuni et al, 1997;Baumgartner, 2000;King et al, 2000;Stefan et al, 2000;Paulini et al, 2007;Ebersole and Ebersole, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…12,13 MEG is a reliable indicator of the presence of interictal spikes on electrocorticography (ECoG) and can be used to plan intracranial electrode placement. [14][15][16] MEG spike dipoles have been correlated with the ictalonset zone on intracranial video-electroencephalography (EEG). [17][18][19] Because FCD type II is intrinsically epileptogenic, MEG has been successfully employed to localize the irritative zone noninvasively during presurgical evaluation.…”
mentioning
confidence: 99%